Identifying and retargeting transcriptional hot spots in the human genome. Issue 8 (30th June 2016) - Cheng, Joseph K.; Lewis, Amanda M.; Kim, Do Soon; Dyess, Timothy; Alper, Hal S.
Abstract: Mammalian cell line development requires streamlined methodologies that will reduce both the cost and time to identify candidate cell lines. Improvements in site‐specific genomic editing techniques can result in flexible, predictable, and robust cell line engineering. However, an outstanding question in the field is the specific site of integration. Here, we seek to identify productive loci within the human genome that will result in stable, high expression of heterologous DNA. Using an unbiased, random integration approach and a green fluorescent reporter construct, we identify ten single‐integrant, recombinant human cell lines that exhibit stable, high‐level expression. From these cell lines, eight unique corresponding integration loci were identified. These loci are concentrated in non‐protein coding regions or intronic regions of protein coding genes. Expression mapping of the surrounding genes reveals minimal disruption of endogenous gene expression. Finally, we demonstrate that targeted de novo integration at one of the identified loci, the 12 th exon‐intron region of the GRIK1 gene on chromosome 21, results in superior expression and stability compared to the standard, illegitimate integration approach at levels approaching 4‐fold. The information identified here along with recent advances in site‐specific genomic editing techniques can lead to expedited cell line development. Abstract : Transgene expression is the crux of the bio‐pharmaceutical industry, and having established integration loci can accelerate cell line development. In this study, the authors identified several integration loci that support elevated transcriptional activity by randomly integrating a fluorescent reporter protein. Subsequently, one particular locus was targeted for de novo integration of two reporter proteins using the CRISPR/Cas9 system and site‐specifically integrated clones exhibited increased reporter production when compared to randomly integrated clones, highlighting the ease of adopting this approach to expedite cell line development.